2011
DOI: 10.1002/jso.21866
|View full text |Cite
|
Sign up to set email alerts
|

Is neoadjuvant chemotherapy prior to radio‐chemotherapy beneficial in T4 anal carcinoma?

Abstract: T4 anal carcinoma can be treated with a curative intent using a sphincter-sparing approach of CRT, and neo-adjuvant chemotherapy should be considered prior to radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
(53 reference statements)
0
8
0
Order By: Relevance
“… 32 A retrospective study conducted by Moureau‐Zabotto L et al revealed that patients who received ICT had a statistically significant better 5‐year CFS in France. 33 In the present study, 10 patients received ICT before CCRT and might contribute to a better survival (Figure S3 ). As most patients with ASCC were diagnosed as locally advanced, we believe that more active systemic treatment was necessary.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“… 32 A retrospective study conducted by Moureau‐Zabotto L et al revealed that patients who received ICT had a statistically significant better 5‐year CFS in France. 33 In the present study, 10 patients received ICT before CCRT and might contribute to a better survival (Figure S3 ). As most patients with ASCC were diagnosed as locally advanced, we believe that more active systemic treatment was necessary.…”
Section: Discussionmentioning
confidence: 65%
“…In 2005, a Swedish study suggested that platinum‐based neoadjuvant chemotherapy could improve the CR rate (92% vs. 76%, p < 0.01) and 5‐year OS rate (63% vs. 44%, p < 0.05) for anal cancer with T ≥ 4 cm or N + compared with radiotherapy ± bleomycin 32 . A retrospective study conducted by Moureau‐Zabotto L et al revealed that patients who received ICT had a statistically significant better 5‐year CFS in France 33 . In the present study, 10 patients received ICT before CCRT and might contribute to a better survival (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies and a recent meta-analysis have examined the use of chemotherapy without radiation in the neoadjuvant setting in the treatment of anal cancer, and there seems to be no clear advantage [37,38]. However, patients with T4 lesions, in special circumstances, may benefit from induction chemotherapy [37].…”
Section: Chemotherapymentioning
confidence: 99%
“…Retrospective studies and a recent meta-analysis have examined the use of chemotherapy without radiation in the neoadjuvant setting in the treatment of anal cancer, and there seems to be no clear advantage [37,38]. However, patients with T4 lesions, in special circumstances, may benefit from induction chemotherapy [37]. Patients who have been treated with prior pelvic radiation and those who are minimally symptomatic or have widespread systemic disease may be candidates for this approach.…”
Section: Chemotherapymentioning
confidence: 99%
“…The lack of benefit of induction chemotherapy before CRT was cemented by the UNICANCER ACCORD 03 trial [26]. The exception might be T4 tumours, which may benefit from neoadjuvant treatment (5FU plus cisplatin) with lower colostomy rates [27]. In the ACCORD 03 study, intensification of the radiation boost to 20-25 Gy (total dose of 65-70 Gy) vs 15 Gy (total dose of 60 Gy) was also tested and proved not to have a significant effect on tumour response, although there was a suggestion of better 3-year colostomy-free survival.…”
Section: Introduction Abstractmentioning
confidence: 99%